Answering Damarin’s Call: How iOS Apps Approach Diversity, Equity, and Multiculturalism - Cherner, Todd; Fegely, Alex (International Journal of Multicultural Education, 2018)
In 1998, Suzanne Damarin put forward a call for technologists and multicultural educators to work together to create technologies that promote inclusiveness and equity for students. As significant technological advancements have happened along with major changes in educational policy over the past 20 years, this study set out to examine if Damarin’s call has been answered. In this article, the researchers first explain how they systematically identified a group of iOS applications designed for iPads and analyzed them for their design quality and content through a lens of diversity, equity, and multiculturalism. They then share their findings and offer implications before concluding with a response regarding the status of Damarin’s call.